Kanonik Jan z Lublina i jego tabulatura - Grajewski, Czesław (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The following article is devoted to Jan of Lublin and his collection of musical notation of different compositions called Jan of Lublin’s tablature. The author presents Canon Jan and his relationship with the monastery of Regular Canons in Kraśnik. The article also focuses on the tablature itself. It discusses the issue of its origin, its contents – special attention was paid to musical genres, the influence of Western European music on Polish music as well as the original achievements of Polish artists. The article is a presentation of a sixteenth-century written text.